The effect of medicinal herb on fat deposition, meat composition, amino acid and fatty acid composition of broiler meats - Santoso, U.; Fenita, Y.; Kususiyah, K.; Widiantoro, O.; Kadarsih, S. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The present study was conducted to evaluate the effect of medicinal herbinclusion on fat deposition, chemical composition, amino acid and fatty acid ofbroiler meats. One hundred-sixty eight female broiler chickens aged 15 days were distributed into 7groups as follows: 1) broilers were fed a diet with no medicinal herb as the control (P0) 2) broilers were fed a diet with 5% Sauropus androgynus leaf powder (P1); 3) broilers were fed a diet with 5% bay leaf powder (P2); 4) broilers were fed a diet with 5% basil leaf powder (P3) 5) broilers were fed a diet with 5% papaya leaf powder (P4); 6) broilers were fed a diet with 5% Moringaleaf powder (P5) and; 7) broilers were fed a diet with 5% noni fruit powder. Experimental results showed that the inclusion of medicinal herbs significantly increased protein (P<0.01), iron(P<0.05), kalium, calcium, phosphorus, linolenic acid(P<0.01), methionine, omega 3 unsaturated fatty acid (P<0.05), but significantly reduced fat (P<0.01), glutamic acid, alanine, lignoceric acid, oleci acid (P<0.01) and omega 9 unsaturated fatty acid (P<0.05). It was concluded that Sauropus androgynus leaf was the most effectiveto produce low fat-high protein and mineral meats.